Analysis of Zakat and Tax Compliance and its Implications for Indonesia’s Fiscal Policy - Fatihah Zakiya Aqmal; Isman; Lukmanul Hakim (www.amertainstitute.com, 2025)
This study aims to analyze the gap between zakat and tax compliance levels in Indonesia’s fiscal policy context in 2021-2024. Based on the latest data, the tax compliance ratio reached 88% in 2023, while the zakat compliance ratio was only 21.7%, indicating a significant gap between the two public financial instruments that should complement each other in the economic system of a Muslim-majority country. This gap indicates a clash between the ideality of applying Islamic economic principles in fiscal policy and the reality of implementation in society and fiscal institutions. The main problem to be answered is: Is there a significant influence between tax compliance and zakat compliance in Indonesia? How have Islamic economic principles been used as a normative and operational framework in tax policy and zakat management to achieve the goals of social justice and economic sustainability? This research is exploratory and analytical (need to do) with a mixed methods approach. Quantitative data measures the compliance ratio and its correlation, while qualitative data examines policies, institutional systems, and public perceptions through literature studies. This research concludes the root of compliance inequality and provides integrative policy recommendations to optimize the role of zakat in the national fiscal system. The benefit of this research is that it will strengthen Indonesia’s fiscal policy to align with Islamic economic values by increasing the contribution of zakat to equitable and sustainable development.